Legal Nature and Regulatory Models of Zero-Hours Contracts in a Comparative Legal Perspective - Shamatava, Irakli; Ivanidze, Mariam; Gulbatashvili, Nino (European Scientific Journal, ESJ, 2026)
A zero-hours contract is a form of non-standard employment under which the employer is not obliged to provide a minimum number of working hours, while the performance of work depends on operational needs and fluctuations in labour demand. Although widely used in several European jurisdictions, Georgian labour legislation does not specifically regulate this contractual model. This regulatory gap creates significant theoretical and practical challenges regarding its labour-law qualification and the protection of employees as the weaker party to the employment relationship. The purpose of this study is to determine the labour-law qualification of zero-hours contracts and to distinguish them from Service Agreements. The research is based on doctrinal, comparative-legal, and functional methods. It examines the regulatory approaches of the United Kingdom, Ireland, Germany, and the Netherlands, together with international labour standards and contemporary doctrinal perspectives. The findings demonstrate that a zero-hours contract does not constitute an independent labour-law institution. Its legal qualification must be determined according to the actual substance of the relationship. Where characteristics such as subordination, personal performance, organisational integration, and economic dependence are present, the relationship should be classified as an employment relationship regardless of the contractual label used by the parties. The study concludes that the existing legal framework of Georgia allows relationships arising from zero-hours contracts to be assessed through the general criteria of an employment relationship. However, the absence of specific regulation creates a risk of legal uncertainty and highlights the need for safeguards that balance labour-market flexibility with employee protection.